Design of patch antennas array at low frequency application by using unknown FR4 material - Hock G.C.; Tho N.T.N.; Charabarty C.K.; Kiong T.S. (2023)
In this paper, a dual patch as the element of the antennas array at low frequency application is presented. An advanced electromagnetic simulation tool is used to model the structure. The array antennas are designed in order to operate at the dual frequency of 457 MHz and 471 MHz. The array antennas consist of six single elements of microstrip patch antenna in order to resonant at both of the frequencies ranges. The design of the array antennas is fabricated on FR4 substrate material with unknown dielectric constant. With the computer-aided tool, the microstrip patch antenna is fine-tuned in order to obtain superior simulation and measurement results. 2011 IEEE.